2019
DOI: 10.5572/ajae.2019.13.3.212
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the National Air Pollutant Emission Inventory (CAPSS 2015) and the Major Cause of Change in Republic of Korea

Abstract: In 2015, air pollutant emissions in the Republic of Korea were 792,776 metric tons of CO, 1,157,728 metric tons of NOx, 352,292 metric tons of SOx, 604,243 metric tons of TSP, 233,177 metric tons of PM10, 98,806 tons of PM2.5, 15,934 metric tons of BC, 1,010,771 metric tons of VOCs, and 297,167 metric tons of NH3. Among major emission source categories, the main emission sources and the contributions to emissions, by pollutant, were as follows: road transport (31.0%), biomass burning (29.3%), and non-road tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The recently updated Korean emission inventory Clean Air Policy Support System (CAPSS; Lee et al, 2011;Yeo et al, 2019) based on the year 2015 also showed a high BC/CO ratio of 25.1 ng m −3 ppb −1 (Table 3), with much lower hypothetical CO emission factors for gasoline vehicles (1.1 CO g km −1 ) and motorcycles (1.7 CO g km −1 ) with similar mean mileage values (30.4 km d −1 ; TS, 2016), suggesting that BC and CO emissions still need to be improved. This high BC/CO ratio (35.6 ng m −3 ppb −1 ) was also found in the MIX emission inventory, whereas the BC/CO ratio from the EDGAR inventory in 2010 was much closer to the measured ratio of 7.68 ng m −3 ppb −1 .…”
Section: Comparison Between the Reas Version 21 And Measured Bc/ Co mentioning
confidence: 99%
“…The recently updated Korean emission inventory Clean Air Policy Support System (CAPSS; Lee et al, 2011;Yeo et al, 2019) based on the year 2015 also showed a high BC/CO ratio of 25.1 ng m −3 ppb −1 (Table 3), with much lower hypothetical CO emission factors for gasoline vehicles (1.1 CO g km −1 ) and motorcycles (1.7 CO g km −1 ) with similar mean mileage values (30.4 km d −1 ; TS, 2016), suggesting that BC and CO emissions still need to be improved. This high BC/CO ratio (35.6 ng m −3 ppb −1 ) was also found in the MIX emission inventory, whereas the BC/CO ratio from the EDGAR inventory in 2010 was much closer to the measured ratio of 7.68 ng m −3 ppb −1 .…”
Section: Comparison Between the Reas Version 21 And Measured Bc/ Co mentioning
confidence: 99%
“…It should be noted that the hot spots in spring and winter were found at the National Industrial Complex in Yeosu (127.67 • E, 34.76 • N) and Gwangyang (127.77 • E, 34.92 • N), which are located approximately 80 km southwest of Gwangju and emitted a large amount of NOx based on the REAS emission inventory (red circle in Figure 5j). The NOx emission rates from Yeosu and Gwangyang from the Clean Air Policy Support System (CAPSS; [59,60]) were 69 Gg yr −1 (31 and 38 Gg yr −1 , respectively), which is similar to that from Seoul (77 Gg yr −1 ) but much higher than that from Gwangju (10 Gg yr −1 ) (https://airemiss.nier.go.kr/ (accessed on 31 August 2020)). Therefore, the NO 2 emitted from the industrial complex had a continuous and significant effect on the air quality in Gwangju, but the magnitude could differ according to the NO 2 lifetime (high in winter and low in summer).…”
Section: Discussionmentioning
confidence: 99%
“…The clean air policy support system (CAPSS) emission inventory [28] was used to generate the gridded anthropogenic emission of South Korea. The Korea-United States air quality study (KORUS-AQ) anthropogenic emission inventory [29] was used for the rest of the region.…”
Section: Gmaf Configuration and Input Datamentioning
confidence: 99%